Assessment of iron overload in a cohort of Sri Lankan patients with transfusion dependent beta thalassaemia and its correlation with pathogenic variants in HBB , HFE, SLC40A1, and TFR2 genes - Ruwangi Dissanayake; Nayana Samarasinghe; Samantha Waidyanatha; Sajeewani Pathirana; Nilaksha Neththikumara; Vajira H. W. Dissanayake; Kalum Wetthasinghe; Lallindra Gooneratne; Pujitha Wickramasinghe (BMC, 2022)
Abstract Background Iron overload (IO) is a complication in transfusion dependent beta thalassaemia (TDT). Pathogenic variants in genes involving iron metabolism may confer increased risk of IO. The objective of this study was to determine the magnitude of the cardiac and hepatic IO and determine whether pathogenic variants in HFE, SLC40A1 and TFR2 genes increase the risk of IO in a cohort of TDT patients in Sri Lanka. Materials and Methods Fifty-seven (57) patients with TDT were recruited for this study. Serum ferritin was done once in 3 months for a period of one year in all. Those who were ≥ 8 years of age (40 patients) underwent T2* MRI of the liver and heart. Fifty-two (52) patients underwent next generation sequencing (NGS) to identify pathogenic variants in HBB, HFE, SLC40A1 and TFR2 genes. Results The median age of the patients of this cohort was 10 years. It comprised of 30 (52.6%) boys and 27 (47.4%) girls. The median level of serum ferritin was 2452 ng/dl. Hepatic IO was seen in 37 (92.5%) patients and cardiac IO was seen in 17 (42.5%) patients. There was no statistically significant correlation between serum ferritin and hepatic or cardiac IO. Thirty-two (61.5%), 18 (34.6%), 2 (3.8%) of patients were homozygotes, compound heterozygotes and heterozygotes for pathogenic variants in the HBB gene. Eight (15.4%) and 1 (1.9%) patients were heterozygotes for pathogenic and likely pathogenic variants of HFE genes respectively. There were no pathogenic variants for the TfR2 and SLC40A1 genes. The heterozygotes of the pathogenic variants of the HFE were not at increased risk of IO. Conclusions Cardiac T2* MRI helps to detect cardiac IO in asymptomatic patients. It is important to perform hepatic and cardiac T2* MRI to detect IO in patients with TDT. There was no statistically significant correlation between pathogenic variants of HBB and HFE genes with hepatic and cardiac IO in this cohort of patients.